Case-control study of occupational exposures and male breast cancer. Issue 9 (September 1998) - Cocco, P; Figgs, L; Dosemeci, M; Hayes, R; Linet, M S; Hsing, A W
Abstract : OBJECTIVE: To investigate whether risk of male breast cancer is associated with workplace exposures. METHODS: A case-control study of 178 cases of male breast cancer and 1041 controls was carried out with data from the United States national mortality follow-back survey, which collected questionnaire information from proxy respondents of a 1% sample of all 1986 United States deaths among subjects aged 25-74 years. Occupational exposure to electromagnetic fields, high temperatures, polycyclic aromatic hydrocarbons (PAHs), herbicides, other pesticides, and organic solvents was assessed by applying job-exposure matrices, based on the 1980 United States census occupation and industry codes, to the longest job held by study subjects as reported by the informants. A socioeconomic status index was created by combining information on annual family income, education, assets, and occupation to assess the association of socioeconomic status with male breast cancer. Relative risks were derived from logistic regression modelling, which included age, socioeconomic status, marital status, and body mass index, as well as occupational exposures. RESULTS: Risk for male breast cancer increased significantly with increasing socioeconomic status index (test for trend: p < 0.01), but the risks associated with individual socioeconomic status variables were smaller and the trends were not significant. A significant increase in risk of male breast cancer was associated with employment in blast furnaces, steel works, and rolling mills (odds ratio (OR) 3.4; 95% confidence interval (95% CI) 1.1 to 10.1, based on six cases), and motor vehicle manufacturing (OR 3.1; 95% CI 1.2 to 8.2, based on seven cases). However, exposures to electromagnetic fields, high temperature, PAHs, herbicides, other pesticides, and organic solvents were not associated with risk of male breast cancer. CONCLUSIONS: The role of workplace exposures in increasing risk of breast cancer among men employed in motor vehicle manufacturing and in blast furnaces, steel works, and rolling mills deserves further investigation. The finding on socioeconomic status suggests that, as well as reproductive factors, other lifestyle factors such as diet that may be related to high socioeconomic status in men should be investigated further.